ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL PERSAMAAN LINEAR DUA VARIABEL DI SMPN 1 CAMPAKA MULYA-CIANJUR - Asep Yusuf; Nelly Fitriani (IKIP Siliwangi, 2020)
This Mathematics is a learning that is very important for everyone, because mathematics is always used in everyday life. But in reality, until now there are still many who think that mathematics is difficult because of the many formulas that must be memorized. Even though the main thing in mathematics is not a formula but a concept in mathematics itself. The purpose of this study is to analyze the students' mistakes in completing the Two Variable Linear Equation System (SPLDV) material in junior high school students, because this material is one of the material that is often used in daily life. The subjects of this study were students of class IX-B at SMPN 1 Campaka Mulya-Cianjur, amounting to 27 people, who were then sampled as many as 6 people representing high, medium, and low ability students to be analyzed. The method used in this research is a case study. The instrument to get the data itself is done by tests given to students in the form of question sheets containing 3 contextual questions with questions that have different levels of difficulty. Based on the trials that have been carried out it turns out that the mistakes of students in solving SPLDV questions are different. From the results of the test there were 2 students with high abilities, 2 students with medium ability, and 23 students with low ability